Assessment of the Economic Structure of Brazilian Agribusiness - Vilmar Rodrigues Moreira; Ricardo Kureski; Claudimar Pereira da Veiga (The Scientific World Journal)
This paper presents an economic assessment of Brazilian agribusiness and its relationship with other economic sectors. It was found that, in 2011, agribusiness had a share of 18.45% (basic prices) and 19.77% (market prices) of Brazilian GDP. The tax burden of agribusiness (20.68%) was higher than that of other sectors (13.59%), despite agribusiness being a major contributor to the generation of foreign exchange, employment, and essential products, such as food. Brazilian agribusiness is a major employer, responsible for 29.39% of national employment. However, its average income is lower than in the other sectors of the Brazilian economy. Finally, agribusiness was found to be the biggest generator of foreign exchange, with a positive balance of trade. It was possible to conclude that agribusiness forms a strong link between agriculture and livestock, industry, and services in other economic sectors. For this reason, it can be said that the development of agribusiness is highly relevant to the process of Brazilian economic development and is therefore important to the progress of economic policies.